Methane reduction from ruminant microbiota of sheep using polyphenols extract of different olive mill wastewater - Selma Hamimed; Amani Kthiri (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
Olive oil production generates considerable quantities of olive mill wastewater, a powerful pollutant dumped in nature without any prior treatment. Olive mill wastewater is considered as a potential source of natural products of high additive value, due to their content of phenolic compounds and other natural antioxidants. This study aims to investigate the impact of phenolic substances, extracted from different olive mill wastewater of different olive varieties, on the composition of the ruminal microbiota of sheep. The results of the quantification of phenolic compounds show the richness of the three varieties (Sigoise, Azzeradj and Chemlal) in polyphenols with respective values of 26.3, 23.97 and 20.09 g/L. Moreover, a stimulation in the fermentative activity was reported, which caused a significant reduction in methane production (24 hours of incubation) of 7.31, 39.36 and 30.06% for Sigoise, Azzeradj and Chemlal, respectively. In addition, this decrease creates a reduction in the production of ammonia and the number of protozoa.